2022
DOI: 10.1007/s12687-022-00579-y
|View full text |Cite
|
Sign up to set email alerts
|

Patient-facing genetic and genomic mobile apps in the UK: a systematic review of content, functionality, and quality

Abstract: Close relative (consanguineous) marriage is widely practised globally, and it increases the risk of genetic disorders. Mobile apps may increase awareness and education regarding the associated risks in a sensitive, engaging, and accessible manner. This systematic review of patient-facing genetic/genomic mobile apps explores content, function, and quality. We searched the NHS Apps Library and the UK Google Play and Apple App stores for patient-facing genomic/genetic smartphone apps. Descriptive information and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…To give an indication of how many apps is reasonable to review, we previously identified 236, 25 405, 24 555, 23 668, 19 754 20 and 3938 26 health apps from initial searches, before screening or deduplication took place. One of our reviews identified 7561 apps before screening 27 due to the topic (exercise), for which many apps exist.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To give an indication of how many apps is reasonable to review, we previously identified 236, 25 405, 24 555, 23 668, 19 754 20 and 3938 26 health apps from initial searches, before screening or deduplication took place. One of our reviews identified 7561 apps before screening 27 due to the topic (exercise), for which many apps exist.…”
Section: Resultsmentioning
confidence: 99%
“…Two of our reviews informed wider research studies; a review of apps used to support hand hygiene to provide the focus for a subsequent research evaluation, 19 and a review of patient-facing genetics apps to inform the design and development of a genetic counselling app. 20 Our other app reviews have provided evidence alongside a more traditional systematic review of the published research literature or as an independent review to guide clinicians/patients about mHealth apps they could use to support patient care.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, we use examples from our previous work as case studies, to highlight and discuss the methodological issues raised when conducting a review of commercially available health apps (see Table 1). Two of our reviews informed wider research studies; a review of apps used to support hand hygiene to provide the focus for a subsequent research evaluation [19], and a review of patient-facing genetics apps to inform the design and development of a genetic counselling app [20]. Our other app reviews have provided evidence alongside a more traditional systematic review of the published research literature or as an independent review to guide clinicians/patients about mHealth apps they could use to support patient care.…”
Section: Methodsmentioning
confidence: 99%
“…Gasteiger & Vercell et al, 2022 [20] To identify patient-facing smartphone apps related to genetic or genomic conditions available in the UK and explore their purpose, functions, and quality.…”
mentioning
confidence: 99%
See 1 more Smart Citation